Indigenous approaches for the management of termite and white grub in upland rice - Mahapatro, G . K; Sreedevi, Kolla (My University, 2014)
Termites and white grubs are of regional importance in upland rain fed rice. Major insect pests in upland rice are stem borers, gundhi bug, mealy bug, root aphids, white grubs, and termites (Odontotermes obesus and Microtermes obesi). The management of the subterranean pests viz., termites and white grubs is challenging in the recent past. In spite of the integrated approach with feasible management options with chemical, biological and cultural methods, both termites and white grubs are posing serious threat to rice in particular upland and rainfed system. The present paper reviews and focus on the indigenous approaches for termite and white grub management, which can find a place in integrated management strategies to curb these soil insect-pest problem.
full text
Keywords: Occurrence, termites, white grubs, Upland rice